Mathematics Engagement among Secondary Student: A Comparative Study based on Socioeconomic Status - Jay Singh; Michael Tarance Suraj; Sangeeta Chauhan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Engagement of students in mathematics is an important determinant which affects academic success as well as the motivation of students in secondary schools. On the other hand, there is inadequate information about the role played by socio-demographic variables like social category and parental occupation in determining student engagement. The objective of this research was to study the differences between social categories and parental occupation on student engagement in mathematics among secondary school students. This research was undertaken using quantitative methodology with a descriptive survey research design. The sample consisted of 211 students of class IX who were taken from two UP Board schools located in Lucknow district. The selection of participants was made through purposive sampling method. The data was collected from the subjects through the tool “Student Engagement in Mathematics Scale” (Perception Scale) designed by Dr. Gurpreet Kaur & Dr. Ram Mehar. Analysis of data was carried out using non-parametric statistical methods, more specifically, Mann–Whitney U test. The result showed that no significant difference was seen in cognitive and behavioral engagement based on social category, however, a significant difference was seen in affective engagement with students of reserved social category having higher engagement. Moreover, there was no observed difference among the dimensions of engagement when categorized according to the job status of parents. In summary, social category and the jobs that the parents have cannot influence engagement except for affective engagement. As a result, creating positive emotions is crucial in enhancing engagement among students.